Analysis Of Competency, Innovation, Market Orientation, And Motivation On The Performance Of Papuan Nutmeg (Myristica Argantea) Communities In Fakfak District - Ali Fuad; Sri Rahayu; Choirul Anam; Putri Rahma Dayanti (RTTM, 2024)
The research aims to determine how much influence competence, innovation, market knowledge and motivation have on the ability of the people of Fakfak regency to realize downstream Papuan nutmeg, in order to obtain added value that can strengthen regional economic development. The research design uses a semi-quantitative analysis approach. The description explains the relationship between research variables which is the result of correlation analysis using the Spearman method. The description also explains qualitatively and in depth the things represented in the regression equation model obtained from the SPSS version 2.3 tool calculations. The results of research during the research show that the real conditions of the work culture of the nutmeg farming community and other nutmeg business actors; just carrying out the same activities for years, even for generations. This resulted in efforts to downstream and increase the scale of production that could already be controlled, basically never happening. The willingness and ability to do business to obtain added value from downstream production of Papuan nutmeg is very low, due to the fear of not knowing the market, and limited access to working capital.